ANALISIS SISTEM INFORMASI MANAJEMEN DIGITAL DALAM PEMENUHAN KEBUTUHAN NASABAH PT. BANK NATIONALNOBU, Tbk CABANG CENTRAL PLAZA BANDAR LAMPUNG - Andy Fitriyadi Dharma Tilaar; Then Ines (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
One of the risks that so far have not been widely anticipated is a failure of bankingtransactions through information technology (technology fraud) which in banking risk including as riskoperational category.The application of information system management digital as part of information technologyin internet banking will improve the efficiency, effectiveness, and productivity as well as increase therevenue by sales system which is more effective than conventional banks.The use of internet in technology makes consumer more comfortable and fulfill of customerneeds because of technology can be used anytime and anywhere without worry of late in doingtransaction. In this case the bank needs to increase security and facilities so that the quality of ebanking services will always be maintained.